Escapement patterns of red mullet, sole, horse mackerel and hake facing two trawl selective devices. (June 2020) - Méhault, Sonia; Kopp, Dorothée; Morfin, Marie; Cuillandre, Jean Pierre; Larnaud, Pascal; Morandeau, Fabien; Vacherot, Jean Philippe; Rimaud, Thomas
Abstract: The landing obligation implemented under the European Union Common Fisheries Policy prompted the development of selective devices for fishing gear to reduce unwanted catches. In the Bay of Biscay, a collaborative project between scientists and fishermen evaluated catch rates and length frequencies of caught species from two innovative trawl devices, which were compared to the gear that is currently used in the fishery. The experimental designs were: (1) a 90 mm square mesh bycatch reduction device inserted in the tapered section (SMBRD) and (2) a 70 mm T90 mesh codend and extension (T90). Each selective device was tested separately using the twin trawl method for catch comparison on board commercial vessels: SMBRD was tested on board vessels targeting Nephrops and T90 on board vessels targeting demersal fish. This study focused on hake ( Merluccius merluccius ), which is an important bycatch species, red mullet ( Mullus surmuletus ) and common sole ( Solea solea ), which have high commercial value, and horse mackerel ( Trachurus trachurus ), which is nearly never discarded. Horse mackerel and hake escaped through the two devices tested, resulting in fewer unwanted catches in the selective trawls without commercial loss. For sole, more individuals were caught with the SMBRD than with the standard gear. The T90 resulted in the escapement of most red mullet across its entire length range observed, resulting in significantly lower Catch Per Unit Effort of landings and unwanted catch, probably due to unsuitable mesh size and shape for that species. These results have direct application for multispecies fisheries in which fishermen have to appropriately select devices according to the specific characteristics and species composition of their fisheries.